Hope incarnate : a systematic theological investigation in conversation with Jurgen Moltmann and Russel Botman - Saaiman, Granville Monrico (Stellenbosch : Stellenbosch University, 2020)
Thesis (MTh)--Stellenbosch University, 2020.